Global respiratory syncytial virus-associated mortality in young children (RSV GOLD): a retrospective case series. Issue 10 (October 2017) - Scheltema, Nienke M; Gentile, Angela; Lucion, Florencia; Nokes, D James; Munywoki, Patrick K; Madhi, Shabir A; Groome, Michelle J; Cohen, Cheryl; Moyes, Jocelyn; Thorburn, Kentigern; Thamthitiwat, Somsak; Oshitani, Hitoshi; et al.
Summary: Background: Respiratory syncytial virus (RSV) infection is an important cause of pneumonia mortality in young children. However, clinical data for fatal RSV infection are scarce. We aimed to identify clinical and socioeconomic characteristics of children aged younger than 5 years with RSV-related mortality using individual patient data. Methods: In this retrospective case series, we developed an online questionnaire to obtain individual patient data for clinical and socioeconomic characteristics of children aged younger than 5 years who died with community-acquired RSV infection between Jan 1, 1995, and Oct 31, 2015, through leading research groups for child pneumonia identified through a comprehensive literature search and existing research networks. For the literature search, we searched PubMed for articles published up to Feb 3, 2015, using the key terms "RSV", "respiratory syncytial virus", or "respiratory syncytial viral" combined with "mortality", "fatality", "death", "died", "deaths", or "CFR" for articles published in English. We invited researchers and clinicians identified to participate between Nov 1, 2014, and Oct 31, 2015. We calculated descriptive statistics for all variables. Findings: We studied 358 children with RSV-related in-hospital death from 23 countries across the world, with data contributed from 31 research groups. 117 (33%) children were from low-income or lower middle-income countries, 77 (22%) were from upper middle-income countries, and 164 (46%) were from high-income countries. 190 (53%) were male. Data for comorbidities were missing for some children in low-income and middle-income countries. Available data showed that comorbidities were present in at least 33 (28%) children from low-income or lower middle-income countries, 36 (47%) from upper middle-income countries, and 114 (70%) from high-income countries. Median age for RSV-related deaths was 5·0 months (IQR 2·3–11·0) in low-income or lower middle-income countries, 4·0 months (2·0–10·0) in upper middle-income countries, and 7·0 months (3·6–16·8) in high-income countries. Interpretation: This study is the first large case series of children who died with community-acquired RSV infection. A substantial proportion of children with RSV-related death had comorbidities. Our results show that perinatal immunisation strategies for children aged younger than 6 months could have a substantial impact on RSV-related child mortality in low-income and middle-income countries. Funding: Bill & Melinda Gates Foundation.